2000
DOI: 10.1038/sj.gt.3301096
|View full text |Cite
|
Sign up to set email alerts
|

Long-term phenotypic correction of rodent hemiparkinsonism by gene therapy using genetically modified myoblasts

Abstract: Rat myoblasts were genetically modified to express tyrosine hydroxylase (TH) and produce dopamine in culture. Implanting TH gene-transfected myoblasts into the denervated striatum of 6-OHDA-lesioned rats significantly decreased rotational asymmetry by 50 to approximately 60%. Improvement persisted for up to 13 months. Genetically modified cells could survive and express transgene in the striatum as demonstrated by RT-PCR and immunohisto-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Several studies have indicated that transfected primary myoblasts grafted into the CNS survive and maintain transgene expression up to several weeks [33, 38]. Tyrosine‐hydroxylase (TH)‐expressing myoblasts transplanted into the striata of 6‐OHDA‐lesioned rats were reported to result in pronounced TH expression as well as long‐term amelioration of Parkinsonian symptoms [39]. While these studies document the applicability of myoblast transplantation for localized gene delivery, widespread cell‐based gene transfer to the CNS has remained a challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that transfected primary myoblasts grafted into the CNS survive and maintain transgene expression up to several weeks [33, 38]. Tyrosine‐hydroxylase (TH)‐expressing myoblasts transplanted into the striata of 6‐OHDA‐lesioned rats were reported to result in pronounced TH expression as well as long‐term amelioration of Parkinsonian symptoms [39]. While these studies document the applicability of myoblast transplantation for localized gene delivery, widespread cell‐based gene transfer to the CNS has remained a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Double labelings were confirmed by digital reconstruction in the x-z and y-z planes. [39]. While these studies document the applicability of myoblast transplantation for localized gene delivery, widespread cell-based gene transfer to the CNS has remained a challenge.…”
Section: Figure 6 Confocal Laser Scanning Microscopy Confirming the mentioning
confidence: 99%
“…[28][29][30] These cells are capable of producing and releasing levodopa when exogenous BH 4 is added to the culture medium, and, when implanted in 6-OHDA-lesioned rats, behavioral recovery was observed. [32] In both reports, behavioral recovery was observed. Based on this concept, other cell types, such as myoblasts, [31,32] were also engineered to express TH.…”
Section: Symptomatic Therapymentioning
confidence: 90%
“…Interestingly, myoblasts have been transfected with TH alone and stably produce dopamine for more than a year after striatal injection which reduces apomorphine-induced rotation of 6-OHDA-lesioned rats by 50% (Cao et al 2000); no apparent proliferation of grafted cells has been noted. Moreover, positive results from GDNF-expressing encapsulated myoblasts have been reported (Zurn et al 2001).…”
Section: Gene-modified Grafts From Non-neuronal Sourcesmentioning
confidence: 98%